Spinel/Lithium‐Rich Manganese Oxide Hybrid Nanofibers as Cathode Materials for Rechargeable Lithium‐Ion Batteries. Issue 12 (3rd September 2019) - Liu, Junxiang; Wang, Jiaqi; Ni, Youxuan; Zhang, Yudong; Luo, Jun; Cheng, Fangyi; Chen, Jun
Abstract: Lithium‐rich layered oxides are among the most promising cathode candidates to build high‐energy‐density rechargeable Li‐ion batteries but suffer from capacity/voltage fade, low reversibility, and poor rate capability. Herein, the synthesis and electrochemical application of heterostructured spinel/layered oxide (Li1.15 Ni0.20 Mn0.87 O2 ) nanofibers as superior cathode materials are reported. The synergistic effect of 1D nanostructure and spinel/layer heterostructure enhances charge transfer, lithium diffusivity, and structural stability, resulting in improved initial Coulombic efficiency (≈100%), rate performance (150 mAh g −1 at 5C), and cyclability (258 mAh g −1 after 70 cycles). In situ X‐ray diffraction and Raman combined with first‐principle calculations reveal that the spinel stabilizes the layered Li‐rich Mn‐based oxide structure via maintaining oxygen vacancy and suppressing the structural variation and oxygen overoxidation. Abstract : Porous nanofibers of heterostructured spinel and lithium‐rich layered manganese oxide are designed, synthesized, and investigated as superior cathode materials for lithium‐ion batteries.